Study on determination method of phthalates from indoor air by gas chromatograph tandem mass spectrometry technique (GC/MS) - Tran, Tri (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2DO - 10.25073/2588-1140/vnunst.4484, 2017)
In this report, the determination method of phthalates in indoor air has been studied. For air samples, the particulate phase was kept on a quartz fiber filter and the gas phase was collected on two polyurethane foams (PUFs) by a low speed pump during a period of 12 to 24 h. The target compounds were extracted from filter and PUFs by mixture of dichlomethane and n-hexane and performed on a GS/MS system. The method quantification limit of siloxane in the air samples ranged from 1 to 3 ng/m 3 , the linear range of standard solution was from  1 to 1000 ng/mL. The recoveries of method ranged from 67,9% to 117% with a RSD < 9% for both of analysis and surrogate compounds. The optimized method was applied for determination of siloxane in indoor air collected from Hanoi, Vietnam.